2019
DOI: 10.1177/1096348019835600
|View full text |Cite
|
Sign up to set email alerts
|

It’s Raining Complaints! How Weather Factors Drive Consumer Comments and Word-of-Mouth

Abstract: Limited attention has been given to the drivers of customer behavior that originate from less direct factors, such as weather. Weather is known to significantly alter consumers’ moods and consequently their behavior. Building on the theoretical alignment between weather, mood, and consumer behavior, this research examined how specific weather factors drive the valence of consumer comments. Furthermore, we explore the relationship between perceived weather, consumers’ moods and affective experience, and word-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 105 publications
(113 reference statements)
1
16
0
1
Order By: Relevance
“…The findings of the current research showed that the product reviews written after the normalization period were more negative than those in the pre-pandemic period. This result is consistent with studies in the literature (Sundaram et al, 1998;Bujisic et al, 2019) indicating that negative mood affects product reviews. According to another result of the current research, the length of product reviews was affected by the product type.…”
Section: Hypothesis Test Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the current research showed that the product reviews written after the normalization period were more negative than those in the pre-pandemic period. This result is consistent with studies in the literature (Sundaram et al, 1998;Bujisic et al, 2019) indicating that negative mood affects product reviews. According to another result of the current research, the length of product reviews was affected by the product type.…”
Section: Hypothesis Test Resultssupporting
confidence: 92%
“…Pandemi sürecinde insanların ölüm tehdidi ile karşı karşıya kalmaları (Song, Jin, Gao, & Zhao, 2020) ve kendilerini hapisteymiş gibi hissetmeleri (Fullana, Hidalgo-Mazzei, Vieta, & Radua, 2020) Gwinner, Walsh, & Gremler, 2004). Ürün değerlendirmesinin içeriğinin olumlu veya olumsuz oluşu tüketicinin içinde bulunduğu ruh hali ile ilişkilidir (Bujisic, Bogicevic, Parsa, Jovanovic, & Sukhu, 2019;Sundaram, Kaushik, & Webster, 1998). Olumlu veya olumsuz içerikte olmasına ek olarak ürün değerlendirmeleri farklı uzunluklarda yazılabilir.…”
Section: Bulaşma Hızının Ve Enfeksiyon Oranının Yüksekliğinden Dolayı Dünya Sağlıkunclassified
“…The analysis of TripAdvisor reviews to assess climatic sensitivity of tourists has been applied successfully to 19 locations in South Africa (Fitchett & Hoogendoorn, ; ) and to a Ski Resort in Lesotho (Stockigt et al ., ), providing information regarding whether climate is a significant factor in determining tourists’ positive and negative experiences and determining the climatic factors tourists are most sensitive to. This allows for targeted adaptation plans that address the most significant concerns of tourists, and specifically those which would lead to negative ‘word of mouth’ advertisement for the destination (Bujisic et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In practice, weather may be an important driver of online review behaviors, especially for restaurants, because it has a huge effect on human mood (Murray et al, 2010), outdoor activities (Koots et al, 2011), product sales (Li et al, 2017), consumption behaviors (Bahng and Kincade, 2012) and financial behaviors (Kang et al, 2010). And weather has been confirmed to have important effects on the dissemination of positive or negative comments and WOM (Bujisic et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They used a quasi-field experiment to collect data and applied the logit regression model to estimate and examine an individual's likelihood to respond to a mobile promotion considering the effects of sunny, cloudy and rainy weather. Bujisic et al (2019) explored how weather factors such as temperature, rain, pressure, storm, humidity and so on drove the valence of consumer comments in restaurants and revealed that mood mediated the relationship between weather and WOM. As mentioned earlier, Bujisic et al (2019) found that consumers' moods were the mediating factor that explained how weather factors influenced WOM.…”
Section: Introductionmentioning
confidence: 99%